Masīrah al-Ḥajj wa Ta‘thīruhā ‘ala al-Taṭawwur al-Islāmī fī al-Qarnayn al-Tāsi‘ ‘Ashr wa al-‘Ishrīn fī Indūnīsīyā - Ibrahim, Umar (Studia Islamika, 1996)
Pilgrimage in ritual practice is not only valuable but also political, economic, and pedagogical. That's because the Hajj is itself a grand conference attended by millions of people from various parts of the world with a background in economics, politics, social and cultural diversity. This grand congress often used for political interests by Muslim rulers so that this opportunity is most practical political forum to influence, shape and spread of certain patterns of thought to various other parts of the Muslim world. In the 18th century, every year thousands of pilgrims go to Mecca and came home with orthodox Islam which gradually able to shift mistisismedan syncretism previously more prominent in the history of Islamic thought in Indonesia as seen Kalisalak Rifa'i Ahmad (1786-1875). They were also instrumental in mobilizing the masses in the resistance against the invaders.DOI: 10.15408/sdi.v3i1.816